The Mitochondrial Genes BAK1, FIS1 and SFN are Linked with Alterations in Mitochondrial Membrane Potential in Barrett?s Esophagus - Phelan, James; O'Sullivan, Jacintha (My University, 2018)
Barrett’s esophagus and esophageal cancer lack prognostic markers that allow the tailoring of personalized medicine and biomarkers with potential to provide insight into treatment response. This study aims to characterize mitochondrial function across the metaplasia-dysplasia-adenocarcinoma disease sequence in Barrett’s esophagus and examines the functional effect of manipulating mitochondrial genes. Mitochondrial genes of interest were validated in in vitro cell lines across the metaplasia (QH), dysplasia (GO) and adenocarcinoma (OE33) sequence and in in vivo patient tissue samples. These genes were subsequently knocked down in QH and OE33 cells and the functional effect of siRNA-induced knockdown on reactive oxygen species production, mitochondrial mass, mitochondrial membrane potential and cellular metabolism was investigated. Three global mitochondrial genes (BAK1, FIS1 and SFN) were differentially altered across the in vivo Barrett’s disease sequence. We also demonstrate that knockdown of BAK1, FIS1 and SFN in vitro resulted in significant alterations in mitochondrial membrane potential; however, no differences in reactive oxygen species or mitochondrial mass were observed. Furthermore, knockdown of these genes in esophageal adenocarcinoma cells significantly altered cellular metabolism. In conclusion, we found that differential expression of BAK1, FIS1, and SFN were altered across the Barrett’s disease sequence and manipulation of these genes elicited significant effects on mitochondrial membrane potential.
PUBLISHED
Keywords: Barrett's metaplasia; Esophageal cancer; Mitochondrial genes; Mitochondrial dysfunction; Mitochondrial membrane potential; Cancer